Prevalence of congenital muscular dystrophy in Italy: A population study. (3rd March 2015) - Graziano, Alessandra; Bianco, Flaviana; D'Amico, Adele; Moroni, Isabella; Messina, Sonia; Bruno, Claudio; Pegoraro, Elena; Mora, Marina; Astrea, Guja; Magri, Francesca; Comi, Giacomo P.; Berardinelli, Angela; et al.
Abstract : Objective: We provide a nationwide population study of patients with congenital muscular dystrophy in Italy. Methods: Cases were ascertained from the databases in all the tertiary referral centers for pediatric neuromuscular disorders and from all the genetic diagnostic centers in which diagnostic tests for these forms are performed. Results: The study includes 336 patients with a point prevalence of 0.563 per 100, 000. Mutations were identified in 220 of the 336 (65.5%). The cohort was subdivided into diagnostic categories based on the most recent classifications on congenital muscular dystrophies. The most common forms were those with α-dystroglycan glycosylation deficiency (40.18%) followed by those with laminin α2 deficiency (24.11%) and collagen VI deficiency (20.24%). The forms of congenital muscular dystrophy related to mutations in SEPN1 and LMNA were less frequent (6.25% and 5.95%, respectively). Conclusions: Our study provides for the first time comprehensive epidemiologic information and point prevalence figures for each of the major diagnostic categories on a large cohort of congenital muscular dystrophies. The study also reflects the diagnostic progress in this field with an accurate classification of the cases according to the most recent gene discoveries.